Retrospective Analysis of Patients Undergoing Arthroscopic Rotator Cuff Repair at a Single Institution Yields a 0.11% Postoperative Infection Rate - Harsh Singh, B.A; Inis Isak, B.S; William M. Cregar, M.D; John D. Higgins, M.D; Amar S. Vadhera, B.S; Allison K. Perry, B.S; Gregory P. Nicholson, M.D; Brian J. Cole, M.D., M.B.A; Nikhil N. Verma, M.D (Elsevier, 2021)
Purpose: To establish an infection rate following primary arthroscopic rotator cuff repair (ARCR) from a single institutional database and to ascertain whether there is a relationship between the use of preoperative corticosteroid injection (CSI) and the risk of postoperative infection. Methods: All medical records at a single institution were retrospectively reviewed to identify patients who had undergone arthroscopic repair from January 2016 to December 2018. Patient charts were reviewed for CSI treatment within 6 months of surgery, superficial or deep infection within 2 months postoperatively, and specific treatment of the infection. Patient characteristics were summarized by descriptive statistics using means with standard deviations for continuous variables and frequencies with percentages for categorical variables. A χ2 correlation analysis was performed to determine the association between receiving an injection and having an infection. Results: A total of 1773 patients were included for analysis with an average age of 59.24 ± 9.4 years. The overall infection rate was 0.11% (2/1773 patients). Both patients were treated with oral antibiotics. Of the included patients, 616 had a preoperative CSI within 6 months of their surgery, and 102 injections were administered within 1 month of surgery. None of these patients had a postoperative infection. A χ2 correlation analysis showed a negligible relationship between preoperative injections and postoperative infection (φ = 0.02, χ2 = 0.84). Conclusions: Through this single-institution, large cohort retrospective review, we found an overall 0.11% rate of postoperative infection following primary arthroscopic RCR. In addition, we found no correlation between the use of preoperative CSI ahead of elective ARCR at any time point and risk of developing a postoperative infection. Infection is uncommon following ARCR, and preoperative steroid injection did not increase infection risk in our study population. Level of Evidence: Level IV, therapeutic case series.